PERLINDUNGAN HUKUM BAGI KONSUMEN DALAM JUAL BELI APLIKASI PRESET LIGHTROOM DI AKUN INSTAGRAM (STUDI KASUS PADA AKUN INSTAGRAM @PWSTORE1818) - Viana, Wira Okta; Afia, Rahtu (Ensiklopedia Research and Community Service Review, 2025)
Abstract: Legal Protection for Consumers in Buying and Selling Lightroom Preset Applications on the Instagram Account @pwstore 1818, which can be achieved in two ways, through litigation or through court and non-litigation (outside court). For consumer disputes that occur with the owner of the Instagram account, they are resolved non-litigation, namely there is a verbal agreement from both parties, where the owner of the Instagram account returns the money of consumers who have purchased problematic Lightroom presets, so that both parties reach a win-win solution. The obstacle faced by consumers in resolving disputes over the sale and purchase of Lightroom preset applications on the Instagram account @pwstore1818 is related to the case of goods not matching the picture experienced by consumers Jupiter and Vie Kesuma when purchasing Lightroom presets on the Instagram account @pw.store1818. Consumers have submitted complaints but the business actor has not responded. Then the consumer filed a complaint again, in which the complaint received a reply from the business actor who advised consumers to choose a good photo, but the consumer felt that the product they had purchased did not match their expectations. However, there are still some consumers who feel they have really been disadvantaged, so the business actors provide compensation in the form of refunds.Keywords: Legal Protection, Consumers, Buying and Selling.Sinaga.. Jamur Merang dan Budidayanya, Penebar Swadaya, Jakarta, 2001.Perlindungan Hukum Bagi Konsumen Atas Penjualan Produk Tas Obral Online Skripsi Oleh Agustin Nurindah Permatasari 8111414127 Program Studi Ilmu Hukum Fakultas Hukum Universitas Negeri Semarang, 2018.Frans Hendra Winarta, Hukum Penyelesaian Sengketa Arbitrase Nasional Indonesia dan Internasional. Penerbit : Sinar Grafika, Jakarta.. 2012.Harjono. Konstitusi sebagai Rumah Bangsa. Sekretariat Jenderal dan Kepaniteraan Mahkamah Konstitusi. Jakarta, 2008.https://www.ekrut.com/media/preset, diakses tanggal 20 Juni 2023.http://eprints.umm.ac.id/51082/3/3_BAB%20II.pdf.Muhamad Rengge S, Tinjauan Yuridis Perbuatan Melawan Hukum Dalam Jual Beli Rumah,http://eprints.ubhara.ac.id/950/1/KRISPI%20RENGGE%20FINAL%20SEASON%20FULL.pdf.Philipus M. Hadjon.. Perlindungan Hukum Bagi Rakyat Di Indonesia. Sebuah Studi Tentang Prinsip-Prinsipnya. Penanganan oleh Pengadilan dalam Lingkungan Peradilan Umum dan Pembentukan Peradilan Administrasi Negara. PT Bina Ilmu. Surabaya. 1987.Rachmadi Usmani, Mediasi di Pengadilan : Dalam Teori dan Praktik. Jakarta. Penerbit : Sinar Grafika. 2012.Ronny Hanijo Soemitro, Metodologi Penelitian Hukum dan Jurimentri, Ghalia Indonesia, Jakarta, 1990.R. Soeroso, Pengantar Ilmu Hukum, Sinar Grafika, Jakarta, 2011.Setiono. Rule of Law Supremasi Hukum. Tesis Magister Ilmu Hukum Program Pascasarjana Universitas Sebelas Maret. Surakarta. 2004.Suharsimi Arikunto, Manajemen Penelitian, Rineka Citra, Jakarta, 2005.Mohamad Kharis Umardani, “Jual Beli Berdasarkan Kitab Undang-Undang Hukum Perdata Dan Hukum Islam (Al-Quran-Hadist) Secara Tidak Tunai”, Journal of Islamic Law Studies, 2019.Yessi Nadia, Penyelesaian Sengketa Litigasi dan Non-Litigasi (Tinjauan Terhadap Mediasi dalam Pengadilan sebagai Alternatif Penyelesaian Sengketa di Luar Pengadilan, https://www.academia.edu/29831296/Penyelesaian_Sengketa_Litigasi_dan_NonLitigasi_Tinjauan_terhadap_Mediasi_dalam_Pengadilan_sebagai_Alternatif, diakses tanggal  1 Juli  2023.